Lexical Acculturation in Native American Languages. - Brown, Cecil H. (Oxford studies in anthropological linguistics., 1999)
The author of this study explores the nature of acculturation in the encounter between Europeans and Native Americans. Specifically, he examines how Native American languages adjusted to the introduction of foreign objects and concepts after 1492, discerning patterns of linguistics.